2012
DOI: 10.1590/s0103-65132012005000067
|View full text |Cite
|
Sign up to set email alerts
|

Metodologias para seleção de fornecedores: uma revisão da literatura

Abstract: ResumoA crescente participação do fornecedor na perfomance geral da contratante tem tornado as organizações mais exigentes na escolha de seus contratados, o que ocasionou a incorporação de uma diversidade de critérios de avaliação ao processo decisório. A relevância e complexidade da decisão de contratação, por sua vez, têm incentivado a busca por novas ferramentas e técnicas de seleção de fornecedores. Nesse sentido, a presente pesquisa realizou uma revisão literária dos trabalhos desenvolvidos relacionados a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 79 publications
(40 reference statements)
1
10
0
6
Order By: Relevance
“…In the literature, several models have been developing for supplier's evaluation, which use, from weightings, high sophisticate methods with mathematics programming and multi-criteria decision (Viana & Alencar, 2012). For the accomplishment of the present work, it is used the AHP method developed by Thomas L. Saaty, in 1970, indicated to deal with complex decisions (Ware et al, 2012).…”
Section: Use Of Ahp In Supplier Evaluationmentioning
confidence: 99%
“…In the literature, several models have been developing for supplier's evaluation, which use, from weightings, high sophisticate methods with mathematics programming and multi-criteria decision (Viana & Alencar, 2012). For the accomplishment of the present work, it is used the AHP method developed by Thomas L. Saaty, in 1970, indicated to deal with complex decisions (Ware et al, 2012).…”
Section: Use Of Ahp In Supplier Evaluationmentioning
confidence: 99%
“…Ho et al (2010) carried out a literature review on articles published in international journals from 2000 to 2008, the authors found that the most used individual approach was DEA, whereas the most popular integrated approach was AHP -GP, besides the most popular criteria were: quality, delivery, and price/cost. Viana & Alencar (2012) conducted a literature review based on 56 articles on supplier selection problem and identified main methodologies used, trends and gaps of the literature in the period between 1998 and 2011.…”
Section: Supplier Selection Problem (Ssp)mentioning
confidence: 99%
“…A influência que os fornecedores exercem sobre o desempenho do comprador torna cada vez mais relevante o processo de avaliação da base de fornecedores de uma organização. Selecionar e administrar bem os fornecedores são tarefas chave no gerenciamento da cadeia de suprimentos e, por esse motivo, as organizações têm se tornado mais criteriosas em relação à execução de tais tarefas (ORDOOBADI;WANG, 2011;SU;DYER;GARGEYA, 2008;VIANA;ALENCAR, 2012).…”
Section: Avaliação De Fornecedoresunclassified
“…Dentre os diversos critérios utilizados para avaliação dos fornecedores, preço, qualidade e entrega são os mais frequentes (KAKOURIS, 2006;VIANA;ALENCAR, 2012).…”
Section: Problema De Pesquisaunclassified